Epigenetics in age-related macular degeneration - Lotery, Andrew (Henry Stewart Talks, 2017)
Epigenetics: terms and definitions, Evidence for role of epigenetics in age-related macular degeneration (AMD), Future directions (potential for novel treatments for AMD)